Capacity Building of Pokdarwis Birtaria Kassi Jeneponto Regency through CHSE Based Resilient Tourism Management Training - Muhammad Ansarullah S. Tabbu; Fransiska Stepani; Farhah Fauziah; Seti Armaida Kartika; Desi Purnama; Nadira Damayanti A; Muh.Irfan Al-Ashari; Muh. Syahriadi; Ridho Muharram; Adnan Al Khairi; Fikran Basri; Adrian Adrian; Hasruddin Hasruddin; Adiaksa Ali; Muh.Faiz qushayyi; Ishak Kurniawan (PT. Global Research Collaboration, 2024)
This training programme focused on building the capacity of Pokdarwis Birtaria Kassi in Jeneponto District through training on CHSE (Cleanliness, Health, Safety, and Environment Sustainable) based tourism management. Given the importance of sustainable tourism, the training was designed to increase Pokdarwis members' understanding and awareness of CHSE principles. By involving lecturers and students from the PPK Ormawa team of HMJ Geography FMIPAM, the programme implemented a series of training and mentoring activities. The results showed a significant increase in the understanding and application of CHSE among members, which is expected to improve the quality of tourism services and destination competitiveness. This activity also supports the achievement of the College's Key Performance Indicators, providing a broader positive impact to the community and environment in Birtaria Kassi.